Knowledge about Sexual and Reproductive Health among School Enrolled Adolescents in Tololar, Nicaragua, A Cross-Sectional Study - S. Bergström Anna; J. Ugarte Guevara William; Eustachio Colombo Patricia; Källestal Carina (Journal of Public Health International, 2018)
Background Nicaragua has the highest prevalence of teenage pregnancies in Latin America. Knowledge regarding sexual and reproductive health plays an integral part in sexual behavior. The objective was to assess school going adolescents' knowledge about sexual and reproductive health and possible factors affecting it in the semi-rural community of Tololar, Nicaragua. Methods A cross-sectional study with a self-administered questionnaire on tablets was used for data collection. All 253 registered students at the school present at the time of fieldwork who gave written informed consent were deemed eligible for the study. A total of 225 participants in the ages of 11-19 years were included. Simple linear regression and multiple linear regression were performed analyzing the outcome knowledge. A p-value <0.05 was considered significant. Results The general knowledge about sexual and reproductive health was moderate; however, knowledge gaps were found such as prevailing myths and poor knowledge regarding human immunodeficiency virus (hiv) transmission and contraceptive methods. Being female and single were significant negative determinants of knowledge (p-value < 0.01) and knowledge increased significantly with age (p-value < 0.05). School teachers, websites, social networks, and TV were the most frequently chosen sources of information on the topic. Conclusions Increased education on sexual and reproductive health with new interventions particularly for young females is recommended. Using IT-based materials as a complement may be an effective way to reach out to adolescents.
Keywords: adolescent